Risk-Cost of Capital Relation : How JEREMIE and Similar Funds Decrease Cost of Capital Rate for SME - Michalski, Grzegorz (Relacja między ryzykiem a kosztem kapitału : wpływ JEREMIE i podobnych funduszy na finansową sytuację MSP, 2009)
From financial perspective, the JEREMIE fund initiative is profitable and enhances the functioning of micro and small enterprises. Particularly profitable are aspects connected with providing these enterprises with equity capital (i.e. Business Angels, Venture Capital) as well as with the theoretical possibilities connected with reducing the financial risk by over regional institution guarantees (less vulnerable to potential risks occurring in the native region of the micro enterprises engaged in JEREMIE). Key words: capital cost, target capital structure, micro and small enterprises
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 65, s. s. 187-198
Keywords: capital cost; target capital structure; micro and small enterprises